Living Responsibly: Ethical Issues in Everyday Life - Prothmann, Jan, (Inter-Disciplinary Press Philosophy & Religion Special E-Book Collection, 2009-2016, ISBN: 9789004401013., 2014)
\'Everything we do, every decision we make, in every aspect of our lives, affects others, whether or not we think about those effects before acting. Every single move we make has ethical significance. It matters how we behave towards others, including strangers, family and friends; the extent to which we are willing to share what we have; the energy we use in travelling and in heating our homes; where we should shop for food, clothes and the other essentials of modern life. This eBook invites all of us to engage in reflection about these ethical issues of everyday life. Those of us who care about how we affect the world and those with whom we share it will find the issues raised and thoughts offered a source of inspiration. The topics touched upon are wide-ranging, promising innovative ideas for turning the intention to live responsibly into practice. \'